Co-exposure of dimethomorph and imidacloprid: effects on soil bacterial communities in vineyard soil - Chang, Jean; Shen, Fo-Ting; Lai, Wei-An; Liao, Chien-Sen; Chen, Wen-Ching (Frontiers in Microbiology, 2023)
In Taiwan, the pesticides dimethomorph and imidacloprid are recommended for pest control in vineyards. Therefore, tank-mixing of these two pesticides is usually a routine practice before application. This study analyzed the influence of vineyard soil microbial flora under the recommended and high dosages (100 times the recommended dosage) of dimethomorph and imidacloprid. Individual and combined applications of pesticides were also tested through batches of soil incubation experiments. Four treatments—control (C), dimethomorph (DT), imidacloprid (IM), and mixed application of dimethomorph and imidacloprid (ID)—were used in the experimental design. From the soil metabolism, no significant reaction was observed after 2 months in the recommended dosage group, regardless of whether the pesticides were being applied individually or combined. For the high dosage, imidacloprid showed a higher effect than the co-exposure treatments, showing a possible prolonged effect after its repetitive application. From PCoA analysis, pesticide treatments altered the soil ecology after 2 months, and the effect of imidacloprid can be explicitly observed at high dosages. At the phylum level, Acidobacteria can indicate pesticide application around the recommended dosage. It was inhibited by ID on day 7 and was augmented by all pesticides on day 63. The effect of the recommended dosage of pesticide mixtures after 2 months of incubation was revealed in the minor families Gemmataceae and Pirellulaceae, while the high dosage treatments affected both the core and the minor families. Our findings verified the changes in the composition of microbial communities upon pesticide application, which would affect carbon, nitrogen, sulfur, phosphorous cycles, and contaminant removal ability within the vineyard.